“Nice White Ladies Don’t Go Around Barefoot”: Racing the white subjects of The Help (Tate Taylor, 2011) - Marie-Alix Thouaille (Alphaville: Journal of Film and Screen Media, 2015)
Not only is The Help (2009; 2011) a text within which a white woman author (Eugenia “Skeeter” Phelan, played by Emma Stone) profits from the lives of women of colour, but it is also a text originally written by a white woman author (Kathryn Stockett) who profits from the real and/or imagined lives of women of colour. Both authors rely on the invisibility of their whiteness and white privilege in order to inhabit, and, appropriate from, marginalised subjectivities. Through an analysis of The Help’s filmic strategies for inscribing whiteness as a form of absence, this article posits that women of colour are erased and excluded by our continuing cultural reluctance to “see” whiteness and its privileges. I go on to argue that the film simultaneously offers a sceptical reading of Stockett’s and Skeeter’s appropriative projects, finding ways to make characters’ whiteness visible, embodied and accountable. Only in interrogating this cultural invisibility can we contest the ways in which neoliberalism and postracism interplay to reify middle-class whiteness as the default subject position for women in screen media in the twenty-first century.